2018
DOI: 10.3329/bsmmuj.v11i1.35584
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome of mitral valve replacement through right anterolateral thoracotomy versus standard median sternotomy

Abstract: <p class="Abstract">This study was aimed to compare the peri-operative outcomes among the mitral valve replace-ment using anterolateral thoracotomy (n=17) and standard median sternotomy (n=17) in a single surgeons practice. The mean age was 24.1 ± 5.3 years in Group I and 41.0 ± 11.5 years in Group II. Female was predominant in Group I. Total operative time and bypass time were significant in both the study groups. Incision scar was not visible in females in Group I but full incision scar was visible in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(16 reference statements)
2
0
0
Order By: Relevance
“…The by-pass time and total operative time were prolonged in group A versus group B. Similar to our results Saha et al [15] reported a significantly higher mean total operative time of [229.5 ± 28.1 minutes] in Group I versus [197.8 ± 45.0 minutes] in the median sternotomy group. In addition, Ahmad Shah et al [14] reported prolongation of total in thoracotomy than sternotomy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The by-pass time and total operative time were prolonged in group A versus group B. Similar to our results Saha et al [15] reported a significantly higher mean total operative time of [229.5 ± 28.1 minutes] in Group I versus [197.8 ± 45.0 minutes] in the median sternotomy group. In addition, Ahmad Shah et al [14] reported prolongation of total in thoracotomy than sternotomy.…”
Section: Discussionsupporting
confidence: 90%
“…Ahmad Shah et al [14] also reported that cosmetic results were better at thoracotomy group especially at young females who were satisfied with the appearance of the postoperative scar. Saha et al [15] and Ganie et al [16] reported overall slight female sex predominance as in the current work.…”
Section: Discussionsupporting
confidence: 75%